The Effectiveness of Acceptance and Commitment Therapy in Reducing the Symptoms of Attention Deficit Hyperactivity Disorder among Intellectual Gifted Students and Improving their Cognitive Flexibility - Eltantawy, Mahmoud Mohamed; Abd El-Naiem, Hanan Nagy (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
Background: The issue of the presence of attention deficit hyperactivity disorder (ADHD) in intellectually gifted students is a complex one due to the overlap between ADHD symptoms and the characteristics of gifted students. Objective: The current study aimed at reducing ADHD symptoms in intellectually gifted students and improving their cognitive flexibility through Acceptance and Commitment Therapy (ACT) principles and techniques. Methods: The study relied on a quasi-experimental approach to test the effectiveness of ACT principles and techniques in reducing the severity of ADHD symptoms and improving cognitive flexibility. A one-group quasi-experimental design (experimental group) was used with pre- and post-measurement and then follow-up measurement to verify the continuity of the program's effectiveness. The independent variable was the principles and techniques of ACT, while the dependent variables were symptoms of ADHD and cognitive flexibility. The final study sample consisted of (11) intellectually gifted secondary school students with ADHD. Results: The study's results demonstrated the effectiveness of ACT in reducing the severity of ADHD symptoms in intellectually gifted people and improving their cognitive flexibility. Conclusions: This study is one of the first to use ACT to reduce the severity of ADHD symptoms and develop cognitive flexibility among this category of students. The study presented a scale to measure cognitive flexibility among secondary school students and a program based on the principles and techniques of ACT.